Pengaruh Human Capital dan Social Capital Terhadap Intelectual Capital Dengan Organizational Citizenship Behaviour sebagai Variabel Mediasi pada Perangkat Desa di Kabupaten Kerinci - Ayu Esteka Sari; Ida Yusnita; Albetris Albetris (Ekonomis: Journal of Economics and Business, 2022)
The phenomenon of development development is in rural areas. In order to realize national development goals, the government pays the greatest attention to development in the countryside. So that the spearhead of the village is one of them is the Village Device is required to improve the quality of self reflected in human capital, social capital, Intelectual capital and Organizational Citizenship Behavior (OCB). This research aims to find out the Influence of human capital and social capital on Intelectual capital Village Devices With Organizational Citizenship Behaviour as a Mediation Variable on Village Devices in Kerinci Regency. Respondents in this study were Village Devices in Kerinci Regency by taking samples of village devices located in Gunung Raya and Bukit Kerman districts so that 174 respondents were obtained. The Model Testing Technique in this study used the Stuctural Equation Model (SEM). Human capital and social capital had an effect of 98.1% on Organizational Citizenship Behavior (OCB) on Village Devices in Kerinci Regency and Human capital, social capital and Organizational Citizenship Behavior (OCB) had an effect of 15% on Intelectual Capital on Village Devices in Kerinci Regency.